2020
DOI: 10.1002/jbm4.10434
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Scope and Mechanisms of Calcitriol Actions Using Genetically Modified Mouse Models

Abstract: Genetically modified mice have provided novel insights into the mechanisms of activation and inactivation of vitamin D, and in the process have provided phenocopies of acquired human disease such as rickets and osteomalacia and inherited diseases such as pseudovitamin D deficiency rickets, hereditary vitamin D resistant rickets, and idiopathic infantile hypercalcemia. Both global and tissue‐specific deletion studies leading to decreases of the active form of vitamin D, calcitriol [1,25(OH)2D], and/or of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…1,25(OH) 2 D then exerts its principal actions by binding to the vitamin D receptor (VDR). Although 1,25(OH) 2 D deficient [1α(OH)ase -/- ] 12 and VDR deficient (VDR -/- ) 13 mouse models have been generated over 2 decades and have provided considerable insight into the regulation of mineral and skeletal physiology by 1,25(OH) 2 D 14 , 15 , whether OA phenotypes occur in long bone joints of 1α(OH)ase -/- and VDR -/- mice has not been reported. We have previously reported that 1,25(OH) 2 D deficiency may play a role in the pathogenesis of temporomandibular joint OA 16 .…”
Section: Introductionmentioning
confidence: 99%
“…1,25(OH) 2 D then exerts its principal actions by binding to the vitamin D receptor (VDR). Although 1,25(OH) 2 D deficient [1α(OH)ase -/- ] 12 and VDR deficient (VDR -/- ) 13 mouse models have been generated over 2 decades and have provided considerable insight into the regulation of mineral and skeletal physiology by 1,25(OH) 2 D 14 , 15 , whether OA phenotypes occur in long bone joints of 1α(OH)ase -/- and VDR -/- mice has not been reported. We have previously reported that 1,25(OH) 2 D deficiency may play a role in the pathogenesis of temporomandibular joint OA 16 .…”
Section: Introductionmentioning
confidence: 99%